Hippocampal subfield volumes in major depressive disorder and bipolar disorder - Han, Kyu-Man; Kim, Aram; Kang, Wooyoung; Kang, Youbin; Kang, June; Won, Eunsoo; Tae, Woo-Suk; Ham, Byung-Joo (European psychiatry, 2019)
The hippocampus is not a uniform structure, but rather consists of multiple, functionally specialized subfields. Few studies have explored hippocampal subfield volume difference in the same sample of major depressive disorder (MDD) and bipolar disorder (BD) cases. We aimed to investigate the difference of hippocampal subfield volume between patents with MDD and BD and healthy controls (HCs). A total of 102 MDD and 55 BD patients and 135 HCs were recruited and underwent T1-weighted image. Hippocampal subfield volume was calculated by automated segmentation and volumetric procedures developed by Iglesias et al. and implemented in FreeSurfer. Volume differences between the groups were analyzed using the analysis of covariance and controlling for age, sex, and total intracranial cavity volume. Patients with MDD had significantly reduced volumes in the bilateral cornu ammonis 1 (CA1), CA4, the granule cell layer (GCL), molecular layer (ML), whole hippocampus, the left CA2/3, and right presubiclum and subiculum. Patients with BD had significantly reduced volumes in the right CA1, GCL, and the whole hippocampus as compared to HCs. No significant volume differences were observed between the MDD and BD groups. Illness duration was negatively correlated with volumes of the left CA1, CA4, ML, presubiculum, subiculum, and the whole hippocampus in patients with BD. We observed hippocampal subfield volume reductions in both MDD and BD, a finding which more prominent in MDD. The inverse correlation between BD illness duration and hippocampal subfield volume may evidence the neuroprogressive nature of BD.